Gene delivery nanoparticles to modulate angiogenesis - Kim, Jayoung (Adv Drug Deliv Rev, 2016)
Angiogenesis is naturally balanced by many pro- and anti-angiogenic factors while an imbalance of these factors leads to aberrant angiogenesis, which is closely associated with many diseases. Gene therapy has become a promising strategy for the treatment of such a disordered state through the introduction of exogenous nucleic acids that express or silence the target agents, thereby engineering neovascularization in both directions. Numerous non-viral gene delivery nanoparticles have been investigated towards this goal, but their clinical translation has been hampered by issues associated with safety, delivery efficiency, and therapeutic effect. This review summarizes key factors targeted for therapeutic angiogenesis and anti-angiogenesis gene therapy, non-viral nanoparticle-mediated approaches to gene delivery, and recent gene therapy applications in pre-clinical and clinical trials for ischemia, tissue regeneration, cancer, and wet age-related macular degeneration. Enhanced nanoparticle design strategies are also proposed to further improve the efficacy of gene delivery nanoparticles to modulate angiogenesis.